Manager's guide to OSHA - Tompkins, Neville C. (Crisp Pub. Menlo ParkUS, 1993)
Explains the provisions of the Occupational Health and Safety Act (OHSA); discusses employer and employee rights, and responsibilities including OHSA safety and record-keeping requirements. Also outlines the protocols for an OHSA inspection and explains what should be done after an inspection.